Ultrafast Early Warning of Heart Attacks through Plasmon‐Enhanced Raman Spectroscopy using Collapsible Nanofingers and Machine Learning. Issue 2 (4th November 2022) - Liu, Zerui; Meng, Deming; Su, Guangxu; Hu, Pan; Song, Boxiang; Wang, Yunxiang; Wei, Junhan; Yang, Hao; Yuan, Tianyi; Chen, Buyun; Ou, Tse‐Hsien; Hossain, Sushmit; et al.
Abstract: As the leading cause of death, heart attacks result in millions of deaths annually, with no end in sight. Early intervention is the only strategy for rescuing lives threatened by heart disease. However, the detection time of the fastest heart‐attack detection system is >15 min, which is too long considering the rapid passage of life. In this study, a machine learning (ML)‐driven system with a simple process, low‐cost, short detection time (only 10 s), and high precision is developed. By utilizing a functionalized nanofinger structure, even a trace amount of biomarker leaked before a heart attack can be captured. Additionally, enhanced Raman profiles are constructed for predictive analytics. Five ML models are developed to harness the useful characteristics of each Raman spectrum and provide early warnings of heart attacks with >98% accuracy. Through the strategic combination of nanofingers and ML algorithms, the proposed warning system accurately provides alerts on silent heart‐attack attempts seconds ahead of actual attacks. Abstract : Here, an ultrafast early heart‐attack warning system is invented through Surface‐enhanced Raman spectroscopy using collapsible nanofingers and machine learning (ML). By using functionalized nanofinger structure, it allows for trace amounts of biomarkers to be detected. Raman spectra are constructed for predictive analytics using ML models. This system provides alerts on silent heart‐attack attempts with >98% accuracy ahead of actual attacks.